The Impact of the National Strategy for Cybersecurity in Reducing the Risks of Accounting Information Systems - An Empirical Study on thy Saudi Governmental Sector - Barasheed, Nahed Abdullah; Obaid, Rawya Reda (Journal of Risk and Crisis Management, 2025)
The primary objective of this study is to assess the impact of implementing the National Cybersecurity Strategy on reducing the risks associated with accounting information systems (AIS) within government sectors in Saudi Arabia. The study focuses on key aspects of this strategy, including protecting AIS, managing, and evaluating their risks, assessing the quality of their outputs, and determining the availability of qualified personnel to apply cybersecurity strategies to AIS in the Saudi government sector. The study relied on the inductive approach in preparing the theoretical part, where topics and studies related to the research topic were reviewed and analyzed to form the theoretical framework. Meanwhile, the descriptive analytical approach was adopted in the practical aspect. The study population included (300) participants from accountants, financial analysts, internal and external auditors, and specialists in the field of information technology and cybersecurity in a number of government sectors in Saudi Arabia. The results indicated a statistically significant relationship between the studied elements, demonstrating a positive effect of the National Cybersecurity Strategy on protecting accounting information, managing, and assessing risks, and improving the quality of accounting information outputs, contingent upon the availability of qualified personnel to implement the strategy. Consequently, the study confirms that the impact of the National Cybersecurity Strategy on reducing AIS-related risks is a pivotal aspect in Saudi government sectors, given the critical role of accounting information in governance and effective management. The study recommends several measures, including regular training sessions for government employees on the importance of cybersecurity and risk management, investment in the latest cybersecurity technologies to protect AIS from attacks, the establishment of strict and clear security policies that are regularly reviewed to keep pace with cybersecurity developments, and leveraging international expertise and knowledge exchange to adopt best practices in cybersecurity.
Keywords: Information Protection; Accounting Information Systems; Cyber Security; Risk